FERTILIZING BARE LAND AND EX- MINES AS A WAY TO EDUCATE STUDENTS TO LOVE THE EARTH - Karnedi, Dieng (Sanata Dharma University Yogyakarta, 2017)
Ecological destruction is very real today. It is increasing day by day along with many causes. Deforestation and mining are two of them, which truly threaten not only humans but also the environment and biodiversity. To gain awareness and knowledge about ecological destruction and to achieve ecological conversion, action and research study is needed. Related to this concern everyone, including students, must be involved. The aim of this article is to offer a methodical study which is based on research study. Its study is also integrated toward Arbuscular Mycorrhiza Fungi (AMF) which is associated toward pioneer plant like Koro Hijau (Macrotyloma uniflorm) as a unique technology to fertilize bare land and ex-mining. This study can be applied toward senior high school students specifically grade X related to microbiology subject or grade XII related to the growth and development of plants subject. The approach of this study is best applied in practicum class after students have received basic understanding on its subject in theoretical class. AMF application toward pioneer plants to solve bare land and ex-lime mine problems is one of the research studies which is applicable toward education method in school level. Following its method, students are not only able to gain their theoretical and practical knowledge but also able to empower their passion and preference to love and care about environment and earth.DOI: https://doi.org/10.24071/ijiet.2017.010203